Exciton-Phonon Interactions in Monolayer Germanium Selenide from First Principles - Huang, Tianlun Allan; Zacharias, Marios; Lewis, D Kirk; Giustino, Feliciano; Sharifzadeh, Sahar (My University, 2021)
We investigate from first principles exciton-phonon interactions in monolayer germanium selenide, a direct gap two-dimensional semiconductor. By combining the Bethe-Salpeter approach and the special displacement method, we explore the phonon-induced renormalization of the exciton wave functions, excitation energies, and oscillator strengths. We determine a renormalization of the optical gap of 0.1 eV at room temperature, which results from the coupling of the exciton with both acoustic and optical phonons, with the strongest coupling to optical phonons at ∼100 cm-1. We also find that the exciton-phonon interaction is similar between monolayer and bulk GeSe. Overall, we demonstrate that the combination of many-body perturbation theory and special displacements offers a new route to investigate electron-phonon couplings in excitonic spectra, the resulting band gap renormalization, and the nature of phonons that couple to the exciton.
Keywords: Electron-phonon interactions; Energy gap; Germanium compounds; Monolayers; Perturbation techniques; Semiconducting germanium; Wave functions